IGARSS 2003. 2003 IEEE International Geoscience and Remote Sensing Symposium. Proceedings (IEEE Cat. No.03CH37477)
DOI: 10.1109/igarss.2003.1294573
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oil slick signatures in SAR images by fusion of hysteresis thresholding responses

Abstract: A new method is proposed in this paper to detect oil slick signatures in oceanographic SAR images. This method is based on directional behavioural oil slick in the sea surface. Therefore, directional hysteresis thresholding responses are first computed in order to bring to the fore dark spots, and increase pixels connexity in each Freeman direction. Those responses are then merged with the help of a Context Independent Constant Behaviour (CICB) operator. The proposed method is tested on ERS SAR amplitude image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…For each of the 14 dates, these three classes are distinguished with a supervised thresholding algorithm. Both VH and VV polarization images are fed into the algorithm, which is based on hysteresis thresholding [37,46]. In our study, the method combines both spatial and temporal dimensions.…”
Section: Flood Detectionmentioning
confidence: 99%
“…For each of the 14 dates, these three classes are distinguished with a supervised thresholding algorithm. Both VH and VV polarization images are fed into the algorithm, which is based on hysteresis thresholding [37,46]. In our study, the method combines both spatial and temporal dimensions.…”
Section: Flood Detectionmentioning
confidence: 99%
“…The power-tomean ratio being a general measure of homogeneity is used to adjust the threshold. Various authors (Solberg and Solberg, 1996;Solberg and Volden, 1997;Kanna et al, 2003;Nirchio et al, 2005) International Journal of Applied Earth Observation and Geoinformation 11 (2009) This paper introduces a modified formula for the fractal box counting dimension. The method is based on utilization of the probability distribution formula in the fractal box count.…”
Section: Introductionmentioning
confidence: 98%
“…The power-to-mean ratio is a good measure of homogeneity used to adjust the threshold. Various authors (Solberg and Solberg 1996, Solberg and Volden 1997, Kanna et al 2003, Nirchio et al 2005 have reported that for RADARSAT-1 SAR ScanSAR narrow mode, thresholding is done at three different scales. Using three different scales, however, did not work well for ENVISAT satellite data.…”
Section: Introductionmentioning
confidence: 99%